Jose Emilio Araujo The legacy of a leader - Instituto Interamericano de Cooperación para la Agricultura (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Contents: Excellence 2008. Patica Nurtuting a happy spirit APPIICA for everyone. IICA stands for solidarity